Transcatheter left atrial decompression in patients with dilated cardiomyopathy: bridging to cardiac transplantation or recovery. (26th February 2019) - Bauer, Anna; Khalil, Markus; Schmidt, Dorle; Recla, Sabine; Bauer, Jürgen; Esmaeili, Anoosh; Penford, Gemma; Akintuerk, Hakan; Schranz, Dietmar
Abstract: Background: Left atrial congestion results from backward failure in dilated cardiomyopathy. We aimed to evaluate feasibility and efficacy of percutaneous atrioseptostomy to create a restrictive atrial septum defect in management of dilated cardiomyopathy. Methods and results: From June 2009 to December 2016, 27 interventions comprised left atria decompressions in 22 dilated cardiomyopathy patients; 9 females; age: 24 days to 36.9 years; weight: 3–50 kg; NYHA-/Ross class IV (n=16). Mean left ventricular ejection fraction was 21.5±9.7% and brain natriuretic peptide was 2291±1992 pg/ml. Dilated cardiomyopathy was classified as chronic (n=9); acute (n=1) myocarditis; idiopathic (n=5); left ventricular non-compaction (n=4); mitochondriopathy, pacemaker induced, and arrhythmogenic (n=3). Atrioseptostomy was concomitantly performed with myocardial biopsies 6.5 days (±11.7) after admission (n=11). Trans-septal puncture was used in 18 patients; foramen ovale dilatation was done in four patients. Mean balloon size was 11 mm (range 7–14 mm); total procedure time was 133±38 minutes. No procedural complications were observed. Mean left atrial pressure decreased from 15.8±6.8 to 12.2±4.8 mmHg (p=0.005), left/right atrial pressure gradient from 9.6±5.6 to 5±3.5 mmHg; brain natriuretic peptide (n=18) decreased from 1968±1606 to 830±1083 pg/ml (p=0.01). One patient unsuitable for heart transplantation died at home despite additionally performed pulmonary artery banding and three further left atrial decompressions; five patients were bridged to transplantation, two died afterwards. Functional recovery occurred in the remaining 14 patients and in six after additional pulmonary artery banding. No patient required assist device. Conclusions: Percutaneous left atrial decompression is an age-independent, effective palliation treating patients with dilated cardiomyopathy.